Evaluasi Peraturan Daerah Nomor 7 Tahun 2021 tentang Penanggulangan Anak Jalanan, Gelandangan dan Pengemis di Kota Pasuruan Jawa Timur - Sugiono Sugiono; Nihayatus Sholichah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This research aims to analyze the implementation of social rehabilitation programs for persons with physical disabilities at the Social Affairs Office of Pasuruan City, East Java. Persons with physical disabilities face various challenges in accessing public services and participating in social life, thus requiring comprehensive rehabilitation programs. Using the implementation theory of George C. Edward III, this study examines four critical factors: communication, resources, disposition, and bureaucratic structure. This qualitative research employs a descriptive approach with data collection through in-depth interviews, participant observation, and documentation study. Informants include officials from the Social Affairs Office, rehabilitation program staff, persons with physical disabilities as program beneficiaries, and community members. The results indicate that the implementation of social rehabilitation programs has been running according to established procedures, including physical rehabilitation services, vocational training, and social assistance provision. However, several obstacles were identified, including limited budget allocation, inadequate accessibility of rehabilitation facilities, shortage of trained social workers, and lack of public awareness regarding disability issues. The program has successfully provided assistive devices to 85 beneficiaries and vocational training to 60 persons with physical disabilities in 2023. This study recommends strengthening coordination between related agencies, increasing budget allocation, improving facility accessibility, and conducting socialization to enhance community participation in supporting persons with physical disabilities.